Inhibition of PMN-elastase activity by semisynthetic glucan sulfates - Becker, Markus; Franz, Gerhard; Alban, Susanna (Thrombosis and Haemostasis, 2003)
Proteolysis of connective tissue by enzymes such as PMN-elastase (PMNE) is a crucial step during inflammation and metastasis. Semisynthetic sulfated carbohydrates (SC) were shown to exhibit potent antiinflammatory and antimetastatic activity in vivo. The aim of the present study was to examine whether interferences with PMN-elastase may contribute to these effects. Therefore, the interactions of these compounds with PMNE were evaluated in various test systems. Besides semisynthetic α-1,4/1,6- and β-1,3-glucan sulfates, UFH, a LMWH and pentosan polysulfate (PPS) were included in the study. The inhibitory activity of SC improves not only with increasing molecular weight (MW 10 – 250 kDa: 37 – 54% inhibition at 0.25 µg/ml) and degree of sulfation (DS 0.25 - 2.0: 16 - 50% inhibition at 0.25 µg/ml), but depends also on their genuine polysaccharide structure (IC50 β-1,3-glucan sulfate 0.18 / α-1,4/1,6-glucan sulfate 0.25 / UFH 0.5 µg/ml). Using physiological substrate assays (collagen, elastin), β-1,3- and α-1,4/1,6-glucan sulfates are more active than UFH (inhibition at 1.5 µg/ml: 41 / 32 / 12%). According to enzyme-inhibitor binding studies, SC exhibit structure dependent affinity to the enzyme (Kd for PMNE: β-1,3 < α-1,4/1,6 < UFH). Finally, SC were shown to inhibit cancer cell-mediated elastinolysis.
Keywords: PMN-elastase; glucan sulfates; heparin; inflammation; metastasis